Temperature Influence in the Deactivation of LTA Commercial Zeolites - Nascimento, Beatriz Oliveira (2021)
In an industrial process it is common the utilization of adsorption fixed bed with zeolitic material for gas drying and the adsorbent regeneration may be conducted using a TSA process, which in its turn, can cause the loss of activity, like an aging process. So, the goal of this study is promoting the premature aging of a commercial zeolite, LTA type, by cycles of heating and cooling at two different temperatures, 523 and 573 K. It was made the crystallinity study, textural characterization, FTIR spectroscopy, TGA and carbon dioxide isotherms at 298 K as the probe molecule, to evaluate the adsorption capacity. The crystallinity study does not show any changes in the crystal structure of the zeolite. So, the reduction in the adsorption capacity could be associated to an organic compound deposit in the porous of the material, which might cause the block effect. The temperature study presents a slight variation in the results, but this is not the only factor in the aging process. The number or the duration of the cycles might be key variables in the optimization of this study.